2020
DOI: 10.1186/s12911-020-01175-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an electronic coding algorithm to identify the primary indication of orthopedic surgeries from administrative data

Abstract: Background Determining the primary indication of a surgical procedure can be useful in identifying patients undergoing elective surgery where shared decision-making is recommended. The purpose of this study was to develop and validate an algorithm to identify patients receiving the following combinations of surgical procedure and primary indication as part of a study to promote shared decision-making: (1) knee arthroplasty to treat knee osteoarthritis (KOA); (2) hip arthroplasty to treat hip osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Patients with serious spine pathology or absolute indication for surgery, such as CES, signs of CES such as bowel or bladder incontinence, fracture, infection and malignant neoplasms were excluded over 365 days preceding and including the date of index diagnosis (online supplemental table 2). 39 Patients with conditions that could alter the CSMT or surgical approach and/or increase the odds of lumbar surgery were also excluded: lumbar fusion, arthrodesis or post-laminectomy syndrome,40 41 lumbar spine trauma42 and degenerative lumbar scoliosis and spondylolisthesis 43. As an additional measure of ensuring patients had no previous discectomy, we excluded patients with any instance of discectomy occurring over any time available in the dataset preceding and including the index date of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with serious spine pathology or absolute indication for surgery, such as CES, signs of CES such as bowel or bladder incontinence, fracture, infection and malignant neoplasms were excluded over 365 days preceding and including the date of index diagnosis (online supplemental table 2). 39 Patients with conditions that could alter the CSMT or surgical approach and/or increase the odds of lumbar surgery were also excluded: lumbar fusion, arthrodesis or post-laminectomy syndrome,40 41 lumbar spine trauma42 and degenerative lumbar scoliosis and spondylolisthesis 43. As an additional measure of ensuring patients had no previous discectomy, we excluded patients with any instance of discectomy occurring over any time available in the dataset preceding and including the index date of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…A definition for the outcome of lumbar discectomy was developed based on discussion among coauthors and comparison with previous publications (online supplemental table 4). 36 39 46 47 This definition included multiple procedure codes for discectomy, as well as the ICD-10-PCS code 0SB4* which includes open, percutaneous and percutaneous endoscopic approaches to excise lumbosacral disc material,48 and the Healthcare Common Procedure Coding System code C9757 for lumbar discectomy with implantation of an annular closure device 47. Feasibility testing was conducted in June, 2021, to ensure these codes were represented in the TriNetX database.…”
Section: Methodsmentioning
confidence: 99%
“…CPT and ICD‐10 have high consistency and using both code sets has been shown to increase the sensitivity of procedural case identification. 26 Since HNS was a new surgical option, we decided to compare it to the most commonly performed sleep surgeries prior to HNS, which were palate and multi‐level surgeries. 27 The three cohorts were patients who underwent palate surgery (palate cohort) those who underwent palate and tongue base surgery (multilevel cohort), and patients who received an HNS device (HNS cohort).…”
Section: Methodsmentioning
confidence: 99%
“…The usage of both CPT (HCPCS Level I) and ICD‐10‐PCS procedure codes was chosen as a best practice to comprehensively capture procedures when physician or facility billing were in different systems. CPT and ICD‐10 have high consistency and using both code sets has been shown to increase the sensitivity of procedural case identification 26 . Since HNS was a new surgical option, we decided to compare it to the most commonly performed sleep surgeries prior to HNS, which were palate and multi‐level surgeries 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The time window was set to survey patients outside the immediate recovery period, but not too long after the procedure. Study staff identified patients using a validated algorithm to search electronic health records for relevant ICD and CPT codes, and confirmed eligibility with a limited chart review [ 13 ]. Eligible patients who had undergone TJR were then randomly selected to be included in the study, stratified by surgeon, site, and condition to match the sample size target described in the “Statistical Analyses” subsection below; all eligible patients who had undergone spine surgery were selected for inclusion in the study because of the relatively smaller size of those groups.…”
Section: Methodsmentioning
confidence: 99%